Recepción y Reelaboración del Pensamiento Económicosocial de América Latina en la India, Entre 1960 y 1990 Estudio de Algunos Casos - Deves-Valdes, E (Universidad de Talca, 2012)
This article explores, first, the impact of economic and social thought in Latin America, especially ECLAC and "dependency theory" trends in India. Second, it deals with Indian rewritingof the Latin American production. This is illustrated with comparisons with non-Indian authors that worked with ideas from Latin America. The paper concludes that these notions were received superficially and critically, frequently associated with the scientific and technological problem and they had no significant impact or long-term, as happened with liberalism, Marxism and Social Darwinism.